Contemporary Experience with Cholecystectomy: Establishing 'Benchmarks' Two Decades after the Introduction of Laparoscopic Cholecystectomy. Issue 12 (December 2013) - Udekwu, Pascal O.; Sullivan, William G.
With quality and public reporting of increasing importance, benchmarks are anticipated to grow in relevance. We studied cholecystectomy in a practice in an urban tertiary care hospital. A total of 1083 cholecystectomies were performed in 2008 and 2009. Laparoscopic cholecystectomy was performed in 97.8 per cent of patients with a 2.2 per cent conversion rate. A planned open procedure was performed in only 2.2 per cent of patients. Approximately half of procedures were urgent and performed during an acute hospitalization. Most patients (74%) were female and most patients were overweight or obese (64.8%). Ages into the tenth decade of life were represented. Comorbidities included hypertension, 28.7 per cent; coronary disease, 15.6 per cent; diabetes mellitus, 13.4 per cent; gastroesophageal reflux disease, 10.7 per cent; and asthma, 5.5 per cent. Of female patients, 98 (12.2%) were postpartum and five (0.6%) were pregnant. Of 137 patients without gallstones, 59.1 per cent had biliary dyskinesia and 27 per cent had acalculous cholecystitis. Preoperative magnetic resonance cholangiopancreatography and endoscopic retrograde cholangiopancreatography (ERCP) were performed in most patients with suspected choledocholithiasis. Intraoperative cholangiograms were performed in 6.9 per cent of patients, 3.3 per cent for abnormal liver function studies. Postoperative ERCP was used in most patients with positive intraoperative cholangiograms. All-cause mortality was 0.8 per cent and attributable mortality was 0.2 per cent. Complications occurred in 7.5 per cent of patients, including retained common bile duct stones in 1.1 per cent, bile duct leak in 0.3 per cent, and common bile duct injury in 0.1 per cent.